SUSTAINABLE PROGRAMMES CAN ATTRACT MORE INTERNATIONAL STUDENTS TO MALAYSIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 8 April 2016 Malaysia is fast becoming a higher education hub in the Asian region and this is in line with our aspiration to attract more international students to come to Malaysia.